1993
DOI: 10.1111/jre.1993.28.6.444
|View full text |Cite
|
Sign up to set email alerts
|

Relative avidity of serum antibodies to putative periodontopathogens in periodontal disease

Abstract: Relative a1•idity of serum antibodies to putative periodontopathogens in periodontal disease. J Periodont Res 1993; 28: 444-450. •£) Munksgaard. 1993 ELISA was used to determine both the avidity and titre of lgG, lgA and IgM antibodies to the gram-negative anaerobe. Porphyromonas gingil"alis, in tvllenty periodontitis patients enrolled in a longitudinal study of attachment loss and eleven non-periodontitis affected subjects. The avidity and titre of lgG antibodies to Actinobacillus Actinomycetemcomitans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…Antibody titres to P. gingivalis in the serum samples were ascertained as previously described (Mooney et al. ) with minor modification. Briefly, Dynotech Immunolon 1B microtitre plates (ThermoFisher, Loughborough, UK) were coated overnight with intact P. gingivalis NCTC 11834 (not fixed) at a density of 10 8 /ml in 100 mM bicarbonate buffer pH9.6.…”
Section: Methodsmentioning
confidence: 99%
“…Antibody titres to P. gingivalis in the serum samples were ascertained as previously described (Mooney et al. ) with minor modification. Briefly, Dynotech Immunolon 1B microtitre plates (ThermoFisher, Loughborough, UK) were coated overnight with intact P. gingivalis NCTC 11834 (not fixed) at a density of 10 8 /ml in 100 mM bicarbonate buffer pH9.6.…”
Section: Methodsmentioning
confidence: 99%
“…Antibody titers to P. gingivalis in the serum samples were ascertained as previously described (Mooney et al 1993) with minor modification. In brief, Dynotech Immunolon 1B microtiter plates (ThermoFisher, Leicestershire, UK) were coated overnight with heat-killed P. gingivalis W83 at an OD 600 0.02 in 100mM bicarbonate buffer (pH 9.6).…”
Section: Elisamentioning
confidence: 99%
“…IgG subclasses and their avidity have also been implicated as a factor in periodontal disease progression. Mooney et al (1993) showed that patients who had not experienced attachment loss during a 3‐month monitoring period had anti‐ P. gingivalis antibodies with a higher avidity than those patients who experienced attachment loss. In periodontal disease subjects, it was found that a humoral response involving IgG2 may be ineffective in clearing P. gingivalis infections (Lamster et al 1998).…”
mentioning
confidence: 99%